2022
DOI: 10.3390/ijerph192013047
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Resilience among Respiratory Therapy (RT) Students during Clinical Training in Saudi Arabia: A Nationwide Cross-Sectional Study

Abstract: Background: The epidemic of burnout has been widely documented among health discipline students. However, there is limited information available on the prevalence of burnout and its association with resilience among clinical-level respiratory therapy (RT) students. Methods: Between March 2022 and May 2022, a descriptive, cross-sectional study using a convenience sample of RT students and interns was conducted. A total of 559 RT students and interns from 15 RT programs responded to socio-demographic questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In light of the factors associated with burnout, we found that the prevalence of burnout increases as the GPA of the nursing students and interns increases, which implies the academic performance of the students in a course study. These findings agree with a study done on respiratory therapy (RT) students ( Siraj et al, 2022 ). A possible explanation for this observation is that those individuals with higher GPAs might be pressured by their parents to prepare for the national nursing license exam and have concerns about getting a job and scholarships.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In light of the factors associated with burnout, we found that the prevalence of burnout increases as the GPA of the nursing students and interns increases, which implies the academic performance of the students in a course study. These findings agree with a study done on respiratory therapy (RT) students ( Siraj et al, 2022 ). A possible explanation for this observation is that those individuals with higher GPAs might be pressured by their parents to prepare for the national nursing license exam and have concerns about getting a job and scholarships.…”
Section: Discussionsupporting
confidence: 92%
“…Burnout syndrome is considered a significant public health issue among students pursuing healthcare careers. It is highly prevalent among all health disciplines, including medical and dental ( Bahlaq et al, 2023 ) and RT students ( Siraj et al, 2022 ). According to the current study, moderate to high burnout levels were noted in 88% of nursing students and interns during their clinical training, in concordant with the current literature ( Baudewyns et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported the risk factors of burnout [ 20 , 23–26 , 30 , 31 , 33 ]. Female pulmonologists or respiratory therapists tended to experience more burnout than their male counterparts [ 20 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“… 21 Our findings that RT interns experienced the highest stress level, compared to other academic levels, is because they are expected to act as independent therapists (with no or minimum supervision) with heavy workloads, which may put them under extreme stress. 27 …”
Section: Discussionmentioning
confidence: 99%